Cancer apelin receptor suppresses vascular mimicry in malignant melanoma - Koichi Inukai; Kazuyoshi Kise; Yumiko Hayashi; Weizhen Jia; Fumitaka Muramatsu; Naoki Okamoto; Hirotaka Konishi; Keigo Akuta; Hiroyasu Kidoya; Nobuyuki Takakura; Nobuyuki Takakura; Nobuyuki Takakura; et al. (Pathology and Oncology Research, 2023)
Several reports indicate that apelin is often over-expressed in tumors, and therefore it has been suggested that the apelin–apelin receptor (APJ) system may induce tumor progression. In contrast, our previous research revealed high expression of the apelin–APJ system in tumor blood vessels, suggesting its involvement in the regulation of tumor vessel formation and normalization, resulting in the suppression of tumor growth by promoting the infiltration of T cells. Thus, the effect of the apelin–APJ system on tumors remains controversial. In this report, to clarify the effect of apelin in tumor cells, we analyzed the function of APJ in tumor cells using APJ knock out (KO) mice. In APJ-KO mice, Apelin overexpression in B16/BL6 (B16) melanoma cells induced greater tumor growth than controls. In an APJ-KO melanoma inoculation model, although angiogenesis is suppressed compared to wild type, no difference is evident in tumor growth. We found that APJ deficiency promoted vascular mimicry in tumors. In vitro, cultured APJ-KO B16 cells demonstrated a spindle-like shape. This phenotypic change was thought to be induced by epithelial–mesenchymal transition (EMT) based on evidence that APJ-KO B16 cells show persistently high levels of the mesenchymal maker, Zeb1; however, we found that EMT did not correlate with the transforming growth factor-β/smad signaling pathway in our model. We propose that apelin-APJ system in cancer cells induces tumor growth but negatively regulates EMT and tumor malignancy.